Diretrizes para projeto e desempenho de sistemas construtivos em painéis pré-moldados de concreto : edifícios habitacionais - Strabeli, Giovana Innocenti (Universidade Federal de São Carlos, 2015)
The estimated housing deficit in Brazil was 5.6 million in 2008, in which 83.5% was in urban areas, wherein to meet such demand there is a need for industrialized construction. Prefabricated building systems with precast panels for residential buildings were largely applied in Europe after the Second World War and it has been applied recently in countries of Latin America and Asia. Although construction companies have been using building systems with precast panels for affordable housing in Brazil since the 80´s, the absence of a prescriptive code of practice for design of precast panels demands certification for each system, which needs to meet the performance requirements according to ABNT-NBR 15575:2013. In order to increase the application of prefabricated systems a new Brazilian Code of Practice for Precast Panels, based on international codes, has been concluded and it is now waiting for final approval. In order to achieve optimum performance, constructability and sustainability of the building project there is a need for integration between architectural and structural designs, as well the interaction between product and production, starting from product development based on the analysis of added value for each project until the rationalization of the processes. The level of prefabrication depends on the number and repetition of units. The aim of this research is to identify and define design guidelines based on performance for building systems with precast concrete panels for residential buildings. The literature revision was carried out starting from international references and codes until the study of the Brazilian codes of practice, including the new code for precast concrete panels. In addition, the research presents the main types of panels and typologies for residential buildings with potential to be applied in Brazil. Finally, an example of performance based design for precast concrete panels is presented with some discussions. This study demonstrate that architects and structural engineers can now design building systems with precast panels based on the new codes of practice and numeric simulations without the need of further tests for certification.
Keywords: Concreto pré-moldado; Painéis; Pré-fabricação; Projeto por desempenho; Habitações; Precast concrete; Panels; Prefabrication; Performance based design; Housing; Building systems; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO::PROJETO DE ARQUITETUTA E URBANISMO; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO